APPLICATION COOPERATIVE LEARNING MODEL GROUP INVESTIGATION TYPE ON BASIC COMPETENCE DESCRIBE BASIS PRINCIPLE OF MOTOR FUEL IN CLASS TSM SMK NEGERI 1 PALANGKA RAYA 2016/2017 - Dan Reas; Jhonni Rentas Duling (Jurusan Pendidikan Teknologi Dan Kejuruan, 2017)
The problem is lack of active students in following learning process, where teacher becomes an only source knowledge during in classroom of learning process. One solution is use of the group investigation model, where the group investigation model provides students opportunity to be active and expressing their opinions. The purpose of this study is to find out how the student learning outcomes and student responses by using the model group investigation in class X TSM SMK Negeri 1 Palangka Raya. This type of research is quantitative research. The population in this research is student of class X TKR and X TSM SMK negeri 1 Palangka Raya on academy year 2016/2017 at about 85 students. Based on the results of the study, student learning outcome has increased after using group investigation model on basic competence. It described the basic principles of motor fuel in class X TSM SMK Negeri 1 Palangka Raya with the percentage average completeness of student learning outcomes was reaching 76.55 increased from 47.11 and level of achievement in learning process was at 88,80% before applied group investigation model. With the completeness of learning outcome at 76,55 and level of achievement 88,80 the process of applying model of study group investigation in basic competence has described the basic principles of motor fuel achieving the criteria.